A survival case of invasive thymoma accompanied by acute fulminant myocarditis. Issue 2 (14th September 2013) - Saito, Nayuta; Shimizu, Kenichiro; Kawaishi, Makoto; Araya, Jun; Nakayama, Katsutoshi; Kuwano, Kazuyoshi
Abstract Thymomas are associated with a wide spectrum of autoimmune paraneoplastic diseases. Here we report the case of 31‐year‐old male with invasive thymoma, myasthenia gravis, polymyositis, and acute fulminant myocarditis that presented with cardiogenic shock requiring intra‐aortic balloon pumping and percutaneous cardiopulmonary support. Corticosteroid therapy was effective. To our knowledge, this is the first case of thymoma with acute fulminant cardiomyositis that was successfully treated by assisted circulation and corticosteroids, despite a poor prognosis.